New species and records for the mayfly families Caenidae, Leptohyphidae and Coryphoridae (Ephemeroptera, Pannota) from Venezuelan Guayana’s Uplands - Molineri, Carlos (2011)
We give new geographical and morphological data for the Pannota mayflies of Venezuelan Guayanan uplands. Coryphorus aquilus (Coryphoridae), Amanahyphes saguassu and Tricorythopsis yucupe (Leptohyphidae) are newly recorded for Venezuela, the adults of the last species are described for the first time. Macunahyphes pemonensis sp. nov. and Macunahyphes incognitus sp. nov. (Leptohyphidae) are described from adults from Venezuela and Brazil, respectively. Both new species of Macunahyphes are very nearly related, and are characterized among other features, by the absence of forceps, and the great development of large paired projections on the styliger plate. Caenis teipunensis sp. nov. (Caenidae) is also described from adults, its diagnostic characters include: forceps apically sharp and sclerotized, and very large apophyses of the styliger sclerite. We give new locality records for Tricorythopsis volsellus, previously known from other localities in Venezuela.